Effect of Pressure and Temperature on Shock Wave Propagation in Conducting Gas - Dr. Sarvesh Chandra Yadav; Divya Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study aims to investigate the effects of pressure and temperature on shock wave propagation in conducting gases, focusing on how these variables influence shock wave amplitude, speed, and structure. A theoretical framework is developed to derive the governing equations for shock wave evolution, discontinuity formation, and disturbance propagation, which facilitates an analysis of the gas’s thermodynamic properties and their impact on shock behaviour. The findings reveal that increased pressure steepens the pressure gradient and enhances shock wave strength, while higher temperatures provide gas molecules with additional kinetic energy, altering ionization levels and propagation speeds. The interplay between temperature and pressure significantly affects shock wave dynamics, which is crucial for applications in aerospace, engineering, and astrophysics involving high-energy technologies and propulsion systems. Understanding these dynamics is essential for effectively designing systems that utilize shock waves.